Somijas un Padomju Savienības skrejlapu propaganda Ziemas kara laikā - Turovska, Jekaterina (Latvijas Universitāte, 2017)
Bakalaura darbs “Somijas un Padomju Savienības skrejlapu propaganda Ziemas kara laikā” apskata Somijas un Padomju Savienības skrejlapu propagandu ar Harolda Lasvela (Harold Lasswell) kara propagandas teorijas un Mīke Bāles (Mieke Bal) vēstījuma teorijas palīdzību. Darba mērķis ir analizēt un salīdzināt naratorus, varoņus, tēmas, vietas un attēlus Somija un Padomju Savienības skrejlapās. Analizējot Somijas un Padomju Savienības skrejlapas, redzams, ka abām ir līdzības un atšķirības.

The bachelor thesis “Leaflet Propaganda of Finland and Soviet Union during the Winter War” represents Finnish and Soviet leaflet propaganda with a help of Harold D. Lasswell’s theory about war propaganda and Mieke Bal’s theory of narrative. The goal of the thesis is to analyze and compare narrators, characters, topics, space and pictures in Finnish and Soviet leaflets. During the analysis, it appeared that both Finnish and Soviet leaflets have similarities and differences.
Leaflet Propaganda of Finland and Soviet Union during the Winter War
Keywords: Valodniecība; kara propaganda; skrejlapu propaganda; ziemas karš; vēsture; Somija